Tingkat Kepuasan Calon Pengantin Setelah Mengikuti Bimbingan Pranikah di KUA Kecamatan Cipocok Kota Serang - Imalatul Khairat; Muhayat Muhayat (Jurnal al-Shifa Bimbingan Konseling Islam, 2022)
Premarital guidance services are government programs in realizing happy families, building mutual awareness to create healthy and quality families, overcoming various family conflicts, strengthening commitments, and various life skills to face various challenges of increasingly severe global life. But this is keynot in line with the increasing divorce rate. This study aims to determine how the level of satisfaction of prospective brides after attending premarital guidance services at the Cipocok Religious Affairs Office Serang City. The method used in this study is quantitative descriptive method. The results of this study showed that the level of satisfaction of prospective brides in participating in premarital guidance services was 13% in the very satisfied category, 80% in the satisfied category, 7% in the doubtful category. This shows that most brides-to-be in participating in premarital guidance services are satisfied with the services received.